Antioxidant Activities of Soursop Leaves and Meniran Plant Extracts Combination - Wimpy Wimpy; Livana PH; Putrie Prameswari (GLOBAL HEALTH SCIENCE GROUP, 2022)
Antioxidants can prevent free radicals which from the metabolism of the body, air pollution and contamination of food. Soursop leaves has a good potential as an antioxidant because it contains alkaloids, tannins, flavonoids and saponins. Meniran has a good potential as an antioxidant because it contains alkaloids, tannins, flavonoids and steroids. The combination of soursop leaves extract and meniran extract can provide very strong antioxidant activity than its singular forms. The aim of this study is to determine the antioxidant activity of the combination of soursop leaves extract and meniran extract compared to the singular forms. This research was done at the BPTO Tawangmangu Central Java, Indonesian and Chemical Laboratory, STIKES Nasional from October to December 2016. This type of research was experimental with quota sampling technique. The results showed that IC50 value of singular forms of soursop leaves extract was 116,5376 ppm. IC50 value of singular forms of meniran extract was 30,6893 ppm. IC50 value of combination forms of soursop leaves extract and meniran extract with ratio of 1:1 was 41,4710 ppm. IC50 value of combination forms of soursop leaves extract and meniran extract with ratio of 1:2 was 23,8590 ppm. IC50 value of combination forms of soursop leaves extract and meniran extract with ratio of 2:1 was 56,5174 ppm. The combination of soursop leaves extract and meniran extract had very strong antioxidant activity compared to its singular forms. The combination soursop leaves extract and meniran with ratio of 1:2 had the strongest antioxidant activity.